2020
DOI: 10.1016/j.apergo.2019.102959
|View full text |Cite
|
Sign up to set email alerts
|

Influence of averaging time-interval on shoe-floor-contaminant available coefficient of friction measurements

Abstract: Available coefficient of friction (ACOF) is a common metric of footwear traction performance. ACOF is the ratio of friction to normal force, often averaged over a time-interval. The timeinterval needed to achieve repeatable and valid ACOF is unknown. A post-hoc analysis was performed on nine shoe-floor-contaminant combinations to assess the repeatability and bias of data averaged across 4 time-intervals (2 ms, 50 ms, 100 ms, 200 ms) after the target normal force was reached. The ability to predict human slips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other factors such as a wet roof condition, temperature, friction direction, footwear orientation, individual weight and load may also affect the dynamic CF. Unfortunately, although several methods and devices for the CF measurement have been developed and extensive studies have reported the footwear CFs on various floors (Chang et al, 2016;Gronqvirst et al, 1989;Pollard et al, 2015;Beschorner et al, 2019Beschorner et al, , 2020, a systematical investigation on the dynamic CF under these conditions has not been reported in a sloped roofing environment. This is obviously an urgent and important research project.…”
Section: The Role Of Coefficient Of Friction In Determining the Slip Potentialmentioning
confidence: 99%
“…Other factors such as a wet roof condition, temperature, friction direction, footwear orientation, individual weight and load may also affect the dynamic CF. Unfortunately, although several methods and devices for the CF measurement have been developed and extensive studies have reported the footwear CFs on various floors (Chang et al, 2016;Gronqvirst et al, 1989;Pollard et al, 2015;Beschorner et al, 2019Beschorner et al, , 2020, a systematical investigation on the dynamic CF under these conditions has not been reported in a sloped roofing environment. This is obviously an urgent and important research project.…”
Section: The Role Of Coefficient Of Friction In Determining the Slip Potentialmentioning
confidence: 99%
“…Measurements of both the required and available COF are complicated. The former requires the recruitment of human participants and the use of one or more force platforms so as to analyze the ground reaction force of the foot on the floor [12,13]. The latter, on the other hand, requires the use of a friction measurement device, also called a tribometer or a slipmeter, to measure the COF of the floor under certain footwear and floor conditions [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies testing the effects of the floor, footwear, floor inclined angle, and floor surface contaminations on slipperiness have been reported [14,18,[23][24][25][26][27][28][29][30][31][32]. There were also studies comparing the testing parameters, test methods, reliability, and validity of friction measurement devices [13,17,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%